2020
DOI: 10.13171/mjc101020211198kem
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and insecticidal activity of Anacyclus pyrethrum essential oil from the Bensliman area against Culex pipiens

Abstract: Anacyclus pyrethrum is a herbaceous plant that belongs to the Asteraceae family. The focus of the present study is to extract the essential oil from this plant, to determine its chemical composition and to evaluate its insecticidal activity against the larvae of the mosquito Culex pipiens. The essential oil from A. pyrethrum collected from the region of Bensliman in Morocco was extracted by hydrodistillation and analyzed by gas chromatography coupled to mass spectrometry were studied. Essential oil yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Several studies on the chemical composition of A. pyrethrum have been previously published [ 7 , 8 ], confirming the presence of a wide variety of phytochemicals, of which about one hundred different compounds have been described to date. In traditional medicine, the roots of A. pyrethrum are recommended for treating toothaches, salivary secretions, angina, digestive problems, lethargy, female infertility and even paralysis of the tongue and limbs.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Several studies on the chemical composition of A. pyrethrum have been previously published [ 7 , 8 ], confirming the presence of a wide variety of phytochemicals, of which about one hundred different compounds have been described to date. In traditional medicine, the roots of A. pyrethrum are recommended for treating toothaches, salivary secretions, angina, digestive problems, lethargy, female infertility and even paralysis of the tongue and limbs.…”
Section: Introductionmentioning
confidence: 81%
“…Moreover, its EO production reaches its maximum during the flowering period. In Ben Slimane, in Morocco, this species yields 0.09% of EOs [ 7 ]. In addition, another study found that the EO yield of the spontaneous species collected in Timahdite (Middle Atlas) after flowering (0.07%) is relatively higher than that collected before flowering (0.05%) [ 27 ].…”
Section: Phytochemistry Of Anacyclus Pyrethrummentioning
confidence: 99%
“…Other minor components, including caryophyllene, caryophyllene oxide, and germacrene-D, discourage insect invasion and are effective against common houseflies and mosquitoes as well [ 174 ]. LEO can retard the activities of different neurotransmitters such as acetylcholine esterase and octopamine, activate olfactory receptor neurons, and induce related neurotoxic responses in insects [ 11 , 175 , 176 ]. Concerning this, a recent review [ 11 ] can be referred to for further reading on the insecticidal property of LEO and its underlying mechanism.…”
Section: Leo Therapeuticsmentioning
confidence: 99%
“…Lemongrass essential oil comprises germacrene D (2.24%), caryophyllene (0.57%) and caryophyllene oxide (0.58%) in limited quantity. These bioactive compounds, however, carry substantial insecticidal and repellent activities against various insects, including common housefly and malarial vector mosquitoes (Mokhtari et al, 2020). However, percentage abundance of these constituents can vary depending on the geography, temperature, plant developmental stage, method used for essential oil extraction as well as the solvent used for the extraction (Muturi et al, 2020).…”
Section: Insecticidal Property Of Lemongrass Essential Oilmentioning
confidence: 99%